(647) Are there Laws of Planning? Socialist Planning and its Relevance to Mixed Economics هل هناك قوانين للتخطيط؟ التخطيط الاشتراكي وأهميته للاقتصادات المختلطة - G. Zielinski, Fanusz (INP, 2024)
This paper examines the question of whether there are effective principles of planning that can be valid in any country engaged in national economic planning, regardless of significant differences in socio-political contexts and levels of economic development. The author answers affirmatively, suggesting that some of these principles should be articulated despite their general nature, as they are often neglected or violated in the planning practices of many countries. In the second part of the paper, the applicability of socialist planning to underdeveloped countries will be briefly discussed.